Daylight And Artificial Lighting Integration In Achieving Lighting Uniformity In Educational Building - Hazimah Ulfah Az Zaky; Ova Candra Dewi; Widyarko; Coriesta Dian Sulistiani (Departement of Architecture, Universitas Islam Indonesia, 2023)
Educational buildings in Depok City typically have deep classroom plans, which pose a challenge in achieving good uniformity of lighting distribution throughout the room. Therefore, this study aims to investigate the integration of daylight and artificial lighting to achieve lighting uniformity, especially in classrooms of educational buildings in Depok City. This paper simulated the combinations of Light Shelves (LS), horizontal blind curtains, and artificial lighting dimming systems through Dialux software to explore and discuss the illumination distribution of daylight in the classroom. The combinations were arranged in 7 different strategies and were carried out in average sky conditions. The strategy simulation results show that lighting uniformity is optimally achieved in strategy 3 with 0.74 lux and strategy 7 with 0.72 lux. These results prove an increase in the uniformity of daylight in the classroom by 0.49 lux with LS and 0.58 lux with horizontal blinds but still requires artificial lighting with 50% dimming. Keywords: Dimming; Horizontal blind curtain; Lighting uniformity; Light shelves.